Travailleurs des plateformes numériques de services : quelles garanties sociales ? - Jean-Michel Servais (Revue Interventions Économiques)
The public debate about the social protection of the persons working through electronic platforms providing services focus on the need to protect them, including when there are not covered by an employment contract. The often precarious character of their situation derives from the fact that they depend on their income on one or very few entrepreneurs. The problematic appears to have some similarities with the one, raised for many years, of other workers whose legal status whether as employees or self-employed remains also unclear, including those in the informal economy. The analysis of these experiences informs the present discussion on the guarantees to be offered to the persons studied here, on the possibilities offered by the comparison, but also on their limits. It leads to explore new ways to legislate.